THE PETS:Game Introduction of Pets in Two Languages - Wahyu Febriyanto; Brenda Chandrawati; Erdhi Widyarto (SISFORMA, 2016)
Introducing environment is important for children. Included in this environment is the life of living beings such as humans, animals, and plants. The role of parents is needed in introducing the living creatures. One of the living creatures that endeared children are animals, especially the pets. Therefore made educational game The Pets. With the game "The Pets" is expected to help parents to teach the children in learning about pets based on place of living and food. In this paper describes how to design and create introducing pet game based on the type of food and its habitat in two different languages . "The Pets" has the Android platform with a minimum API Level 14 is created using the game engine Construct 2. Using two dimensional model and image with interesting coloring for children, and using the application CorelDraw X4. From results of the survey, "The Pets" can provide new knowledge and can assist children in learning about pets based on place of living and food. Children who previously could not mention animals vocabulary in English, after playing "The Pets" can name them into English.